Digital Parenting Sebagai Strategi Gender-Sensitive dalam Peningkatan Kapasitas SDM Untuk Pembangunan Berkelanjutan - Adrian Kurnia Sobana Putra; Bagas Saputra; Jauzari Helmi; M Rizky Indrawan Saputra; Wahjoe Pangestoeti (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
The development of digital technology has had a significant impact on how children are educated and supported. Digital parenting strategies are crucial in creating a safe and nurturing environment for the younger generation, while considering gender equality. This study employed qualitative methods with a library approach. It highlights the role of parents in setting boundaries and providing appropriate guidance to children regarding technology use. With a gender-sensitive approach, parents are expected to reduce the gap in technology access and utilization between boys and girls, encourage creativity, and protect children from gender-based risks in the digital world. The implementation of digital parenting strategies aligns with the Sustainable Development Goals, particularly regarding gender equality and women's empowerment.